Fire effect on the grassy and shrubby vegetation in a forest of Caldén (Semiárida, 2020)
The effect of fire in an open woodland of Prosopis caldenia was tested. b The analyzed area is in the northern central part of La Pampa province. The basal cover of grasses and litter increased after fire. Some changes in botanical composition was observed. Piptochaetium napostaense was the most important forage grass in the bottom and the top parts of the burned area. Great changes occurred on the bottom part of the burned area. Forage standing crop was 1064,6 KgMS/ha after.27 months of the fire action. Unburned area was only of 397,2 KgMS/ha. The effect of fire on woody species was notorious. Undesirables shrubs (Larrea divaricata, Condalia microphilla and Schinus jonhstonii) were not killed by fire. Six months later, the coverage of the woody species was 19,1% In the bottom part of the burned area, while the unburned area were 42,2%. No coverage differences were observed between burned and unburned parts of the top area.